A preliminary investigation of Islamic websites' design features that influence use: a proposed model - Aliyu, Mansur; Mahmud, Murni; Md. Tap, Abu Osman; Muhammed Nasser, Rasheed (City University of Hong Kong, 2013)
The growing availability of the Internet and advances in the use of technology among Muslims have led to an increase in the number of websites with an Islamic content. Currently, there is an emerging trend in the improvement of the design and quality of Islamic websites. Islamic websites serve as a medium for Islamic organizations, scholars, and individuals to contribute and participate in several online activities. This research is drawn from the deep understanding that website design is a major factor affecting the use of websites by Muslim users. We therefore investigate the most important design features that influence Muslims to use websites in learning about Islam, as an alternative to the traditional face-to-face learning from scholars and books. Website design is measured by functionality, navigation, interactivity, attractiveness, and organizational features, and website use by the extent to which frequent use is influenced by the website’s design features. An online survey was conducted from November to December 2012. 89 usable responses were collected from faculty members and students at the International Islamic University Malaysia. The participants have experience in using Islamic websites. They were guided to the survey website via the faculty students’ mailing list and Facebook group page. The findings indicate that website attractiveness, functionality, navigation, organizational information, and security/privacy are the most important factors influencing the use of Islamic websites. Interactivity design features were found to be least significant in influencing Muslim users to use Islamic websites for religious purposes. The majority of the Muslim users visit Islamic websites to search for information, seek for scholars’ opinions regarding personal issues/problems (Q&A), and learn about Quran and Hadith. The results of the study are valuable indicators for the direction of future research, and also suggest guidelines for the successful development and adoption of Islamic websites. Keywords: Islamic website, design features, website use, user perceptions